Axial behaviour of Concrete Filled Double Skinned Steel Tubular (CFDST) column with concrete imperfections - Arth J. Patel; Sharadkumar P. Purohit (Fracture and Structural Integrity)
Concrete Filled Double Skinned Steel Tubular (CFDST) composite column is preferred over Concrete Filled Steel Tube composite column (CFST) owing to enhanced strength. However, they may possess concrete imperfection due to shrinkage and creep of concrete and the construction practices adopted. Concrete imperfection may lead to overestimation of strength, reduction in ductility, and composite action of CFDST column. This paper discusses axial compression tests conducted on outer circular and square and inner square-shaped CFDST columns with and without concrete imperfections. Parameters considered in the study include i) shape of the outer steel tube, ii) circumferential gap ratio (1.1% and 2.2%), and iii) spherical or rectangular gap ratio (4.4% and 8.8%). Results of the test in terms of strength, ductility, confinement effect, strain profile along the length, and failure modes are studied in depth. It is observed that the circumferential gap ratio has a significant impact on the peak axial load-carrying capacity of CFDST columns. Ductility of CFDST column reduces with an increase in the concrete imperfection gap ratio. While CFDST columns with circular steel tube yield global buckling failure modes, square outer steel tube exhibit local buckling failure modes. New strength reduction factors are proposed to account impact of circumferential and spherical or rectangular concrete imperfections on load carrying capacity estimation of CFDST column.